Mucospheres produced by a mixotrophic protist impact ocean carbon cycling - Michaela E. Larsson; Anna R. Bramucci; Sinead Collins; Gustaaf Hallegraeff; Tim Kahlke; Jean-Baptiste Raina; Justin R. Seymour; Martina A. Doblin (Nature Communications, 2022)
Marine microbes govern ocean productivity and biogeochemistry, regulating global climate. Here the authors describe the sophisticated feeding strategy of a mixotrophic dinoflagellate and show how its behaviour impacts the vertical flux of carbon.